2016
DOI: 10.1016/j.jgr.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phenolic compound profiles and antioxidative activity of the fruit, leaves, and roots of Korean ginseng (Panax ginseng Meyer) according to cultivation years

Abstract: BackgroundThe study of phenolic compounds profiles and antioxidative activity in ginseng fruit, leaves, and roots with respect to cultivation years, and has been little reported to date. Hence, this study examined the phenolic compounds profiles and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free-radical-scavenging activities in the fruit, leaves, and roots of Korean ginseng (Panax ginseng Meyer) as a function of cultivation year.MethodsProfiling of 23 phenolic compounds in ginseng fruit, leaves, and roots was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 27 publications
8
85
3
Order By: Relevance
“…It has recently been suggested as a potential neuroprotective agent against PD [6] because several studies showed that it has neuroprotective [7], anti-oxidative [8] and anti-inflammatory effects [9]. Korean Red Ginseng (KRG) is steamed and dried Panax ginseng Meyer for lengthy preservation, and our previous study showed that the administration of KRG suppressed dopaminergic neuronal death in SN and ST against MPTP toxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been suggested as a potential neuroprotective agent against PD [6] because several studies showed that it has neuroprotective [7], anti-oxidative [8] and anti-inflammatory effects [9]. Korean Red Ginseng (KRG) is steamed and dried Panax ginseng Meyer for lengthy preservation, and our previous study showed that the administration of KRG suppressed dopaminergic neuronal death in SN and ST against MPTP toxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…More than ten phenolic compounds, including caffeic acid, ferulic acid, vanillic acid, p-hydroxybenzoic acid, gentisic acid, and syringic acid, have been reported in ginseng plants 43–45 . Despite the various biological properties, such as antioxidant and anticancer effects 46 , of the phenolic compounds present in ginseng, the phenolic/aromatic fractions of NOM are believed to be reactive sites for by-product formation 47 and one of the major precursors to the formation of THMs 48 . Furthermore, the temperature of spa water is usually higher than that of swimming water, which facilitates the generation of more volatile organic components from the ginseng samples 49 .…”
Section: Resultsmentioning
confidence: 99%
“…47 In addition to the flavonoids listed in Table 1, a total 23 phenolic compounds have been identified in P. ginseng fruit, leaves, and roots. 48 Ginseng powder (1 g) was extracted with 10 mL of acetonitrile and 2 mL of 0.1 N hydrochloric acid solution using a shaker. The filtrate of the crude ginseng extract was dried and reconstituted with 5 mL of 80% aqueous methanol.…”
Section: 43mentioning
confidence: 99%